(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
Since the end of the Cold War, the role that Europe plays in the world has undergone a complete transformation. The creation of the European Union and its meteoric growth during the period discussed in this book, with the rapid incorporation of states to the initial seed of the European Economic Community, has been a complex process. A reality was created and with it the need to establish a common security architecture in order to preserve said reality – something that has turned into a difficult exercise when faced with the need to meet the interests of the directly involved players: the states.